2000
DOI: 10.1063/1.873843
|View full text |Cite
|
Sign up to set email alerts
|

Whistlerization and anisotropy in two-dimensional electron magnetohydrodynamic turbulence

Abstract: A detailed numerical simulation to understand the turbulent state of the decaying two-dimensional electron magnetohydrodynamics is presented. It is observed that the evolved spectrum is comprised of a collection of random eddies and a gas of whistler waves, the latter constituting the normal oscillatory modes of such a model. The whistlerization of the turbulent spectra has been quantified by novel diagnostics. In this work, results are presented only in the regime where the spatial excitation scales are longe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
73
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(78 citation statements)
references
References 14 publications
5
73
0
Order By: Relevance
“…None of the fully nonlinear calculations, of ourselves or numerous other authors (Biskamp et al 1996(Biskamp et al , 1999Dastgeer et al 2000;Dastgeer & Zank 2003;Cho & Lazarian 2004;Shaikh & Zank 2005;Cho & Lazarian 2009), which have a broad variety of different initial conditions including sufficiently strong magnetic fields, have ever found anything other than a standard Hall cascade. Cumming et al (2004) also consider the possibility of a Hall instability, and its relevance for the evolution of neutron star magnetic fields.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…None of the fully nonlinear calculations, of ourselves or numerous other authors (Biskamp et al 1996(Biskamp et al , 1999Dastgeer et al 2000;Dastgeer & Zank 2003;Cho & Lazarian 2004;Shaikh & Zank 2005;Cho & Lazarian 2009), which have a broad variety of different initial conditions including sufficiently strong magnetic fields, have ever found anything other than a standard Hall cascade. Cumming et al (2004) also consider the possibility of a Hall instability, and its relevance for the evolution of neutron star magnetic fields.…”
Section: Discussionmentioning
confidence: 99%
“…As derived by Goldreich & Reisenegger (1992), the equation governing the magnetic field under the influence of both the Hall effect and Ohmic diffusion is…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous numerical studies of 2 1 2 D decaying EMHD turbulence 8,9,12 have focused on investigating the spectral properties of the energy. These studies have shown that the energy spectrum follows a k Ϫ7/3 decay law for kd e Ͻ1 and k Ϫ5/3 for kd e Ͼ1.…”
Section: Introductionmentioning
confidence: 99%
“…7 Special interest in EMHD has arisen recently to study plasma turbulence. [8][9][10][11][12] Turbulence in a magnetized plasma is in general strongly anisotropic. The scale lengths of the perturbation along the strong field are typically much longer than the scale lengths in the perpendicular plane.…”
Section: Introductionmentioning
confidence: 99%